Drosophila photoreceptor cells exploited for the production of eukaryotic membrane proteins: receptors, transporters and channels - Panneels, Valérie; Kock, Ines; Krijnse-Locker, Jacomine; Rezgaoui, Meriem; Sinning, Irmgard (PLOS ONE, 2011)
BACKGROUND: Membrane proteins (MPs) play key roles in signal transduction. However, understanding their function at a molecular level is mostly hampered by the lack of protein in suitable amount and quality. Despite impressive developments in the expression of prokaryotic MPs, eukaryotic MP production has lagged behind and there is a need for new expression strategies. In a pilot study, we produced a Drosophila glutamate receptor specifically in the eyes of transgenic flies, exploiting the naturally abundant membrane stacks in the photoreceptor cells (PRCs). Now we address the question whether the PRCs also process different classes of medically relevant target MPs which were so far notoriously difficult to handle with conventional expression strategies. - PRINCIPAL FINDINGS: We describe the homologous and heterologous expression of 10 different targets from the three major MP classes--G protein-coupled receptors (GPCRs), transporters and channels in Drosophila eyes. PRCs offered an extraordinary capacity to produce, fold and accommodate massive amounts of MPs. The expression of some MPs reached similar levels as the endogenous rhodopsin, indicating that the PRC membranes were almost unsaturable. Expression of endogenous rhodopsin was not affected by the target MPs and both could coexist in the membrane stacks. Heterologous expression levels reached about 270 to 500 pmol/mg total MP, resulting in 0.2-0.4 mg purified target MP from 1 g of fly heads. The metabotropic glutamate receptor and human serotonin transporter--both involved in synaptic transmission--showed native pharmacological characteristics and could be purified to homogeneity as a prerequisite for further studies. - SIGNIFICANCE: We demonstrate expression in Drosophila PRCs as an efficient and inexpensive tool for the large scale production of functional eukaryotic MPs. The fly eye system offers a number of advantages over conventional expression systems and paves the way for in-depth analyses of eukaryotic MPs that have so far not been accessible to biochemical and biophysical studies.
Gesehen am 07.09.2022